ChemInform Abstract: One‐Pot Synthesis of D‐Glucosamine and Chitobiosyl Building Blocks Catalyzed by Triflic Acid on Molecular Sieves. Issue 20 (20th May 2014) - Despras, Guillaume; Urban, Dominique; Vauzeilles, Boris; Beau, Jean‐Marie
Abstract The method is developed to prepare the building blocks for the construction of oligosaccharides.